The relationship of brand marketing communication and brand authenticity / Wan Soraya Wan Abdul Ghani …[et al.] - Abdul Ghani, Wan Soraya; Azman, Nurul Atiqah Amalina; Mohd Rashid, Norhidayah; Abdul Halim, Abdul Hamid (Universiti Teknologi MARA Shah Alam, 2020)
This study aims to determine the relationship between brand marketing communication towards brand authenticity among the users of a local brand company. Brand marketing communication is related to enhancing the brand itself by shaping the brand authenticity perceptions directly and clarifying its positioning. The survey was conducted among the local coffee brand consumers at a local coffee shop conducting its business in a shopping mall. A sample size of 385 respondents were selected from different ages, races, backgrounds, and statuses in this study by convenience sampling. Four distinct forms of elements in the brand marketing communication were thus reviewed, namely: advertising, social media, sponsorship, and corporate social responsibility. In this research, all the elements showed their respective relationship with brand authenticity, whereby the difference was the extent of the relationships' strength in the results. The results shown were gathered via the latest SPSS software. Further discussions on the results were shared in this paper.